Three essays on public expenditure management - Sicat, Charlotte Justine Diokno; Bautista, Carlos C. (Quezon City Cesar E.A. Virata School of Business, University of the Philippines Diliman, 2016)
Examines why, after 25 years, LGUs are still varied levels of income and development despite the mandate given to local chief executives (LCEs) and locally elected officials. Uses public expenditure management, organization theory and public choice to understand resource allocation, and the consequent outcomes, at the local government level. Tries to answer the questions : How do voter and politician characteristics affect local government decision-making?
Thesis (Doctor of Philosophy in Business Administration)--University of the Philippines Diliman
Keywords: Budget -- Philippines; Expenditures, Public -- Philippines; Finance, Public -- Philippines; Philippines -- Appropriation and expenditures